The Role of Board Structure in Predicting Financial Distress in Malaysia - Md Rus, Rohani (Universiti Utara Malaysia, 2018)
The aim of this study is to examine the impact of board characteristics on financial distress companies.Specifically this study examines board attributes (size of board, percentage of inside directors, CEO is founder, CEO is chairman and CEO duality) and its relation with companies that experienced financial distress after controlling for leverage, market return, lagged of market return, and GDP growth.Compared with previous studies in Malaysia, this study uses PN17 criterion to select the sample and that is defines as the shareholder’s equity is less than 25% of issued and paid-up capital of a firm.Using a data from 2004 to 2009, the results show size and CEO-founder are negatively significantly related to distress while CEO duality and fraction of independent director affect distress positively. This study could be used to measure the effectiveness of The Malaysian Code on Corporate Governance (MCCG).This study is also useful to directors, investors and authorities who would want to know which corporate governance factors explain distress.